Role of financial development in oil-growth nexus in oil-producing economies - Moradbeigi, Maryam (2014)
It is expected that possessing the natural resources could faster the pace of growth in natural resource endowed countries. However, history has shown the opposite outcome for some rich natural resource countries like Nigeria, Iran and Venezuela with low rate of growth in output. On the other hand, there are some countries such as Botswana and Netherland that have managed their rich resources appropriately and enjoyed higher rate of growth. Hence, this raises an interesting question as to why some rich resources countries remained under-developed despite the goodness of resource abundance. Why do some resource abundant countries develop better economic development, while others experience resource curse phenomenon? Why are there heterogeneous experiences among resource rich countries? Recently, financial development not only plays an important role for economic growth, but also is known as one of the sources of resource curse. The main objective of this thesis is to investigate the role of financial development as transmission channel on resource curse in oil-producing economies. The specific objectives are (i) to examine the effect of oil-abundance on financial development in oil producing economies, (ii) to determine the role that financial development plays in mediating the influence of oilabundance on economic growth, and (iii) to evaluate whether financial development can moderate the adverse effect of oil terms of trade growth volatility on economic growth volatility. Motivated by the theoretical arguments that declare a negative impact of natural resources on financial development (e.g. see Nili & Rastad, 2007; and Yuxiang&Chen, 2011), the first objective of this thesis aims to provide some empirical analysis on the relationship between oil-abundance and financial development. In particular, using a core sample of 61 oil-producing economies over the period 1996-2010, this thesis has found a significant adverse effect of oil-abundance on the level of financial development. Countries are more reliant on their oil resources, as captured by the value of oil production divided by GDP as well as the share of oil export in GDP, tend to experience lower level of financial development. The second objective is motivated by the fact that the oil-producing countries with better financial systems have sustained better economic development. Therefore, it is likely that more advanced financial system may moderate the negative effects of oilabundance in the oil-producing economies. However, academic economists have paid very little attention to the role of financial system in mediating the negative impacts of oil on growth. This thesis seeks to find out whether developing good financial system could assist oil-producing economies to escape the negative association between oilabundance and growth. To this end, the interaction term between financial development and oil-abundance is included into the growth model. Using the annual data for a core sample of 63 oil-producing countries over the period 1980-2010, the empirical result indicates that the coefficient of interaction term between financial development and oilabundance is positive and statistically significant. This evidence has suggested the effect of oil-abundance on growth varies in different economies characterized by different level of financial development. An economies with a good financial system can deal more efficiently with the negative impacts of their abundant oil resources on the rate of growth and even can reduce this adverse effect to such an extent that they may turn the curse of oil resource into the blessing and enjoy the positive association between oil and growth in the presence of food financial development. The last objective of this thesis, which is motivated by theoretical arguments that assert the importance of financial development in reducing the economic shocks on the growth volatility (see e.g. Bacchetta&Caminal, 2000; and Beck et al., 2006), aims to provide some empirical evidence on the relationship between oil terms of trade growth volatility and economic growth volatility in different countries with the different level of financial development. Especially, using the five year non-overlapping standard deviation of oil terms of trade growth index and economic growth over the period 1981-2010 for a core sample of 63 oil-producing countries, this study has found a statistically significant positive effect of oil terms of trade growth volatility on the growth volatility. This indicates that the more volatility in oil terms of trade, the more growth volatility. However, when the interaction term between oil terms of trade growth volatility and financial development is included in the model, the coefficient appears to be negative and statistically significant only when the ratio of liquid liabilities in GDP is used as the measure of financial development. Therefore, the empirical results shows weak evidence that countries with good financial system tend to experience lower growth volatility imposed by volatility in their oil resources.